The Role of Local Hydromacrophytes in Leachate Phytoremediation Performed Using Constructed Wetland System - Laily, Sophia; Yanuwiadi, Bagyo; Retnaningdyah, Catur (Graduate School, Universitas Brawijaya, 2017)
The purpose of this research is to analyze the effectiveness of using local hydromacrophytes for performing leachate phytoremediation in constructed wetland (CW) system. It was an ex situ experiment carried out in a glass house by means of free water surface (FWS) CW reactors containing sand and gravel substrates in 3:5 ratio. The reactor was waterlogged by 9 L leachate. The phytoremediation tests were performed in two-factor treatment design involving hydromacrophyte species and hydraulic retention time. Species of local hydromacrophyte used in this research included Alternanthera sessilis, Commelina nudiflora, Paspalum conjugatum, Typha angustifolia and the polyculture of the four species. The improvements in leachate qualities were identified through decreases of physico-chemical parameters. Among the mean values of the percentages indicating the decreases of physico-chemical leachate parameters, the greatest ones were resulted from the treatments using T. angustifolia and A. sessilis on the 30th day. It has proven in the experiment that these two species of hydromacrophyte perform the most effective process of improving leachate quality.Keywords: constructed wetland, leachate, local hydromacrophytes, phytoremediation.